Case Report Outbreak of Winter Coccidiosis in calves from Northwestern Argentina - Olmos, Leandro Hipolito; Avellaneda Cáceres, Agustín; Aguirre Castro, Laura Sabrina; Sandoval, Gabriela Virginia; Medina, Diego M.; Vitulli Moya, Marisol; Colque Caro, Luis Adrián; Micheloud, Juan Francisco (Ediciones INTA, 2022)
Coccidiosis is an intestinal infection caused by protozoans of the genus Eimeria. When the disease occurs in winter, it is known as winter coccidiosis. In July 2021, two calves were referred to INTA-Salta SDVE to determine the cause of death. These animals belonged to a herd that had shown clinical signs, such as bloody diarrhea, poor condition and death. Subsequently, a visit was made to the establishment in which fecal samples were taken on the farm for parasitological studies and a necropsy was performed to another dead animal from the same rodeo. In addition, meteorological data (Tmax, Tmin and Tmed) were collected in the period prior to the death of the animals and at the time of the outbreak. The three necropsied calves showed thickening of the cecum mucosa, colon and rectum, with presence of ulcerations in the cecum mucosa and fibrin clots. Average OPG values were 986.6 (±1693.06), ranging between 0 and 5040 OPG and the most prevalent species was Eimeria zuernii. On the other hand, it was observed that the deaths were related to the moment in which the temperatures decreased. Based on the results of the studies, we conclude that the diagnosis is winter coccidiosis.